2022
DOI: 10.3390/universe8100547
|View full text |Cite
|
Sign up to set email alerts
|

A PeVatron Candidate: Modeling the Boomerang Nebula in X-ray Band

Abstract: Pulsar wind nebula (PWN) Boomerang and the associated supernova remnant (SNR) G106.3+2.7 are among candidates for the ultra-high-energy (UHE) gamma-ray counterparts published by LHAASO. Although the centroid of the extended source, LHAASO J2226+6057, deviates from the pulsar’s position by about 0.3∘, the source partially covers the PWN. Therefore, we cannot totally exclude the possibility that part of the UHE emission comes from the PWN. Previous studies mainly focus on whether the SNR is a PeVatron, while neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
10
2
Order By: Relevance
“…Our estimates for the PWN B-field, based on the PWN's X-ray spatial properties and SED fitting, are not only significantly below what was suggested by Kothes et al (2006) but also below B = 140 μG, which was suggested by Liang et al (2022) based on modeling of the diffusion of relativistic electrons in the PWN. Our disagreement with the Bfield derived from the analysis done by Liang et al (2022) is expected given our different assumptions and models. While Liang et al (2022) incorporated UHE tail emission not necessarily related to the PWN itself within their SED modeling, this paper focuses solely on emission within the general bounds of the PWN region.…”
Section: Constraining Pwn Magnetic Fieldcontrasting
confidence: 54%
See 2 more Smart Citations
“…Our estimates for the PWN B-field, based on the PWN's X-ray spatial properties and SED fitting, are not only significantly below what was suggested by Kothes et al (2006) but also below B = 140 μG, which was suggested by Liang et al (2022) based on modeling of the diffusion of relativistic electrons in the PWN. Our disagreement with the Bfield derived from the analysis done by Liang et al (2022) is expected given our different assumptions and models. While Liang et al (2022) incorporated UHE tail emission not necessarily related to the PWN itself within their SED modeling, this paper focuses solely on emission within the general bounds of the PWN region.…”
Section: Constraining Pwn Magnetic Fieldcontrasting
confidence: 54%
“…While Liang et al (2022) incorporated UHE tail emission not necessarily related to the PWN itself within their SED modeling, this paper focuses solely on emission within the general bounds of the PWN region. Furthermore, unlike the dynamical model used in this paper, the PWN model used in Liang et al (2022) does not include any interaction with the SNR, and the temporal evolution consists only of changes resulting from diffusion and radiative losses.…”
Section: Constraining Pwn Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…As caveats of the model, it was found that the PWN interpretation of LHAASO J2226+6057 leads to a very high radius of PWN, as well as a very small value of magnetic field. Naturally, these results are in contrast with the observational results (Ge et al 2021;Liang et al 2022), thus indicating that the PWN may not be the contributing source to power the UHE gamma-ray source detected. This indicates interaction between SNRs and associated MCs may be the primary reason behind particle acceleration to PeV energies in Galactic sources.…”
Section: Introductioncontrasting
confidence: 79%
“…The break could be caused by the energydependent escape of CRs from SNRs so that a large fraction of low-energy CRs have not reached the molecular clouds (e.g., Ohira et al 2011;Celli et al 2019;Bao & Chen 2021). In addition, PWN or pulsars could serve as the sources of these high-energy CR protons (Cheng et al 1990;Blasi 2000;Amato et al 2003;The LHAASO Collaboration et al 2021;Liang et al 2022).…”
Section: Hadronic Scenariomentioning
confidence: 99%